Additional benefits of repeated-sprint training with prolonged end-expiratory breath holding for improving repeated-sprint ability in semiprofessional soccer players - Lörinczi, F; Vavák, M; Woorons, X. (International Journal of Sports Physiology and Performance, 2025)
Purpose: To investigate the effects of running repeated-sprint training with voluntary hypoventilation at low lung volume (RSH-VHL) including prolonged end-expiratory breath holding (EEBH) on running repeated-sprint ability (RSA).